Russian Multilateral Diplomacy in the Asia-Pacific Regional Integration - Mihoko Kato (Сравнительная политика, 2015)
Russia is a powerful actor of numerous forums, organizations and integration projects in the Asia-Pacific region, that is usually explained by its multilateral diplomacy. The significance of Asia in the Russia's foreign policy is determined by the both external and internal factors. The article analyzes the role of Russia in the Asia-Pacific regional integration projects, as well as historical and political factors of interaction.